Higher interfragmentary compression force improves lateral tibial plateau fracture stability using locking plate fixation: experimental and simulation verification - Daqiang Xu; Jiang Jiang; Zhenhua Ji; Fei Wang; Rui Jia; Hong Hong; Hongtao Zhang; Jianyi Li; Jun Wang (BMC Musculoskeletal Disorders)
Abstract Background This study investigated the impact of higher interfragmentary compression force (IFCF) on the stability of locking plate fixation in lateral tibial plateau fractures. Methods Biomechanical experiments and finite element analysis (FEA) were employed to compare the performance of the AO cancellous lag screw (AOCLS) and a newly developed combined cancellous lag screw (CCLS). Results The results demonstrated that the CCLS provided a higher IFCF without the risk of over-screwing, significantly improving fixation stability. High IFCF markedly increased the initial axial stiffness, allowing for earlier weight-bearing in patients. Additionally, the FEA showed that increased IFCF reduced the peak von Mises stress on implants and the peak equivalent elastic strain on the lateral fragment, thereby enhancing overall structural stability. Conclusions These findings suggested that the CCLS, with its superior IFCF and reduced risk of over-screwing, was a promising option for improving fixation stability in lateral tibial plateau fractures. This improvement could facilitate early rehabilitation, minimise complications, and provide better clinical outcomes. These results provide strong scientific evidence for the clinical use of CCLS.